ADDITIONAL HEAD OF STERNOCLEIDOMASTOID MUSCLE WITH 3RD SUPRACLAVICULAR FOSSA - GULLAPALLI APARNA (International Journal of Pharma and Bio Sciences, 2013)
The sternocleidomastoid acts as a landmark for physicians, surgeons, anesthesiologists and cosmetologists. The variability of sternocleidomastoid may cause complications while trying to access vital structures that are located in the lesser and greater supraclavicular fosse. This case study aims to present a case of additional head of the sternocleidomastoid and discuss its clinical implications. During routine student demonstration dissections, an additional head of sternocleidomastoid was observed in a male cadaver aged about 50 years. This additional clavicular head took origin 2.5cm lateral to the original clavicular head. Because of its presence, 3 supraclavicular fosse were observed. The lesser supraclavicular fossa was between sternal and clavicular heads. Greater supraclavicular fossa was divided into two by the additional head. Sternocleidomastoid with additional head are rare in the literature and may cause severe complications during interventions.